Sex-specific Associations Between Serum Quinolinic Acid and Disease Severity in Relapsing-remitting Multiple Sclerosis: A Cross-sectional Study - Vasić, Marija (Archives of Pharmacy, 2026)
The kynurenine pathway (KP) of tryptophan metabolism generates metabolites with both neuroprotective and neurotoxic properties and has been implicated in multiple sclerosis (MS). However, the relationship between KP metabolites, disease severity, and sex remains unclear. Serum levels of quinolinic acid (QA) and kynurenic acid (KA) were analyzed in a cohort of patients with relapsing-remitting MS. Of the 78 initially recruited patients, biomarker data were available for 40 patients, who were included in the final analysis. Disease severity was assessed using the Multiple Sclerosis Severity Score (MSSS) and patients were stratified into mild-to-moderate (MSSS < 6.7) and a severe disease group. Serum QA and KA concentrations were measured by the enzyme-linked immunosorbent assay (ELISA) and analyzed using two-way ANOVA with Sidak post hoc correction. No significant overall sex-related differences in serum QA or KA levels were observed. KA levels did not differ across MSSS categories. Female patients with high disease severity (MSSS > 6.7) exhibited higher serum QA levels compared with those with lower disease severity (p = 0.032), although this finding was observed in a very small subgroup of female patients (n = 3). These findings suggest a possible sex-related association between elevated serum QA levels and greater disease severity in female patients with RRMS and warrant confirmation in larger studies.